Women's 20Km walking in the 2018 Asian Games comparative analysis of crown and runner-up techniques - Li, X.; Yan, N.; Li, H.-L.; Ding, H.-T.; Sun, J.-N.; Hu, G.-S.; Qin, J.-J. (DEStech Transactions on Social Science, Education and Human Science, 2020)
As one of the advantages of track and field in China, the race walk belongs to the endurance group of the physical fitness-led class. With the continuous innovation of scientific and technological means, the scientification of sports training is becoming more and more perfect, China's race walk has now basically reached the top level, however there is still a certain gap with Europe and the United States. Yang Jiayu, Che Yangshis` sister as the Asian Games women's 20 km race runner-up, is the main athlete of the 2022 Tokyo Olympic Games, although Yang Jiayu won the Asian Games, but there is still a phenomenon of empty fouls, indicating that there are still some technical problems. In order to understand the shortcomings and shortcomings in the sports, Yang Jiayu and Che Yangshi sister technology, and further improve the technical action, this paper to the 2018 Asian Games runner-up as the test object, through the literature method, image analysis method, comparative analysis method and data statistics, To participate in the 2018 Asian Games women's 20km race runner-up's race walking technology research and analysis, their technical characteristics and the famous Russian athlete Kodeyapkina comparative analysis, in order to show the advantages and weaknesses of china's two athletes, so that Yang Jiayu reduce fouls, At the same time, china's two athletes have better race walking technology to participate in domestic and foreign competitions.